(untitled) (Medicine Today, 2024)
Introduction: Gallbladder issues are prevalent globally, particularly in Bangladesh, and become more common with age. Diagnosis involves clinical assessment and confirmation through noninvasive and invasive methods. Understanding gallbladder features is crucial for effective investigation, diagnosis, and management. Objectives: To find out relation between morphological parameters of human gallbladder with age. Materials and Methods: This cross-sectional descriptive study was conducted in the Department of Anatomy in collaboration with the Department of Forensic Medicine, Sylhet MAG Osmani Medical College, Sylhet from January 2014 to December 2014. Fifty human postmortem gallbladders were selected. Dead bodies autopsied within 36 hours of death. Considerable signs of decomposition or decomposed dead body, presence of gross gallbladder disease and any history of poisoning cases were excluded. All the specimens were examined to detect the length, breadth, weight and thickness of the gallbladder; and length and diameter of cystic duct. Results: The study included cadavers ranging in age from 11 to 55 years, with a mean age of 35.02 ± 19.98 years. Of the total, 29 (58.0%) were male, and 21 (42.0%) were female. The length and thickness of the gallbladder increased significantly with age, as did the length and diameter of the cystic duct. But the weight and breadth also change with age, although not significantly. Conclusion: The length and thickness of the gallbladder; the length and diameter of the cystic duct were varied with age; but no variation in weight and breadth. Medicine Today 2023 Vol.36 (1): 31-35